Fully automated process for histamine detection based on magnetic separation and fluorescence detection - Gagic, Milica; Nejdl, Lukas; Xhaxhiu, Kledi; Cernei, Natalia; Zitka, Ondrej; Jamroz, Ewelina; Svec, Pavel; Richtera, Lukas; Kopel, Pavel; Milosavljevic, Vedran; Adam, Vojtech (Talanta, 2020)
To ensure food safety and to prevent unnecessary foodborne complications this study reports fast, fully automated process for histamine determination. This method is based on magnetic separation of histamine with magnetic particles and quantification by the fluorescence intensity change of MSA modified CdSe Quantum dots. Formation of Fe2O3 particles was followed by adsorption of TiO2 on their surface. Magnetism of developed probe enabled rapid histamine isolation prior to its fluorescence detection. Quantum dots (QDs) of approx. 3 nm were prepared via facile UV irradiation. The fluorescence intensity of CdSe QDs was enhanced upon mixing with magnetically separated histamine, in concentration-dependent manner, with a detection limit of 1.6 μM. The linear calibration curve ranged between 0.07 and 4.5 mM histamine with a low LOD and LOQ of 1.6 μM and 6 μM. The detection efficiency of the method was confirmed by ion exchange chromatography. Moreover, the specificity of the sensor was evaluated and no cross-reactivity from nontarget analytes was observed. This method was successfully applied for the direct analysis of histamine in white wine providing detection limit much lower than the histamine maximum levels established by EU regulation in food samples. The recovery rate was excellent, ranging from 84 to 100% with an RSD of less than 4.0%. The main advantage of the proposed method is full automation of the analytical procedure that reduces the time and cost of the analysis, solvent consumption and sample manipulation, enabling routine analysis of large numbers of samples for histamine and highly accurate and precise results.
Keywords: Limit of Detection; Food safety; Spectrometry, Fluorescence; limita detekce; víno; Tellurium; fluorescenční spektrometrie; silany; magnetické jevy; kovové nanočástice; titan; Fluorescence; Wine; Ion exchange chromatography; Ferric Compounds; fluorescenční barviva; Titanium; Fluorescent Dyes; kontaminace potravin; Food Contamination; Maghemite; železité sloučeniny; Cadmium Compounds; Silanes; Histamine; telur; Quantum dots; fluorescence; histamin; Magnetic Phenomena; Quantum Dots; sloučeniny kadmia; kvantové tečky; Metal Nanoparticles